Literature Study Of The Ability Of Fragrant Roots (Vetiveria zizanioides) And Sunflowers (Helianthus Annuus) On Phytoremediation Of Lead-Tainted Soil (Pb) - Yoga, Alif; Voijant Tangahu, Bieby (Riviera Publishing, 2022)
Lead pollution is a serious problem because of its wide distribution as a result of residential, agricultural, and industrial activities. Lead is a heavy metal that can cause various health problems due to its high toxicity. The high level of lead pollution needs to be overcome to reduce the impact of the risk of lead toxicity, one of which is phytoremediation. The ability of vetiver and sunflower in the phytoremediation process of lead has been reported by various literature. 40 kinds of literature were used as data sources. A literature review by making identification and classification based on the variables and parameters that will be reviewed from several articles that discuss the same topic using a synthetic matrix. Both plants have hyperaccumulator properties in absorbing heavy metals. The highest accumulation of Pb was in the roots up to 5500 mg kg-1, while sunflowers accumulated Pb up to 1450 mg kg-1. The accumulation of Pb was influenced by soil type, nutrient abundance, rhizobacteria, and chelating agents. The toxicity of highly contaminated metals did not significantly affect the growth of vetiver but only slightly decreased parameters. Sunflower response to stress caused by Pb varies depending on variety, soil type, metal type, dose, and duration of metal exposure